Stevia residue extract ameliorates oxidative stress in d-galactose-induced aging mice via Akt/Nrf2/HO-1 pathway. (January 2019) - Zhao, Lei; Yang, Huaqing; Xu, Meili; Wang, Xin; Wang, Chengtao; Lian, Yunhe; Mehmood, Arshad; Dai, Haochen
Graphical abstract: Highlights: Stevia residue extract (SRE) is prepared during steviol glycosides production. Chlorogenic acids and caffeic acid were identified as the major components of SRE. SRE ameliorated oxidative stress ind -galactose (d -gal) induced aging mice. SRE promoted the activation of Akt/Nrf2/HO-1 pathway ind -gal treated mice liver. Dietary intake of SRE may be beneficial in preventing or delaying the onset of aging. Abstract: The present study investigated the effect of Stevia residue extract (SRE) against oxidative stress ind -galactose (d -gal) induced aging mice. LC-MS/MS analysis revealed that SRE is a good source of chlorogenic acids. Biochemical results showed that SRE significantly increased the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and total antioxidant capacity (T-AOC), and decreased acetylcholinesterase (AChE) activity and malondialdehyde (MDA) level in serum, liver or brain ofd -gal induced aging mice. At 200 mg/kg, SRE up-regulated the mRNA expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream target genes including GPx1, CAT, SOD1, quinone oxidoreductase-1 (NQO1) and heme oxygenase-1 (HO-1) ind -gal treated mice liver. SRE also up-regulated the protein expression of Nrf2, HO-1 and the ratio of phosphorylated Akt to Akt (pAkt/Akt) ind -gal treated mice liver. These findings suggest that SRE is able to protect against oxidative stress ind -gal induced aging model via activation of Akt/Nrf2/HO-1 pathway. In conclusion, SRE may provide a promising dietary approach for the prevention or alleviation of oxidative stress and age-related conditions.